microRNA-155 Regulates Alpha-Synuclein-Induced Inflammatory Responses in Models of Parkinson Disease - Thome, Aaron D. (J Neurosci, 2016)
Increasing evidence points to inflammation as a chief mediator of Parkinson's disease (PD), a progressive neurodegenerative disorder characterized by loss of dopamine neurons in the substantia nigra pars compacta (SNpc) and widespread aggregates of the protein α-synuclein (α-syn). Recently, microRNAs, small, noncoding RNAs involved in regulating gene expression at the posttranscriptional level, have been recognized as important regulators of the inflammatory environment. Using an array approach, we found significant upregulation of microRNA-155 (miR-155) in an in vivo model of PD produced by adeno-associated-virus-mediated expression of α-syn. Using a mouse with a complete deletion of miR-155, we found that loss of miR-155 reduced proinflammatory responses to α-syn and blocked α-syn-induced neurodegeneration. In primary microglia from miR-155(−/−) mice, we observed a markedly reduced inflammatory response to α-syn fibrils, with attenuation of major histocompatibility complex class II (MHCII) and proinflammatory inducible nitric oxide synthase expression. Treatment of these microglia with a synthetic mimic of miR-155 restored the inflammatory response to α-syn fibrils. Our results suggest that miR-155 has a central role in the inflammatory response to α-syn in the brain and in α-syn-related neurodegeneration. These effects are at least in part due to a direct role of miR-155 on the microglial response to α-syn. These data implicate miR-155 as a potential therapeutic target for regulating the inflammatory response in PD. SIGNIFICANCE STATEMENT The main feature associated with Parkinson's disease (PD) is the accumulation of α-synuclein in the brain accompanied by signs of inflammation and immune activation. Our studies suggest that microRNA-155 is a key inflammation-initiating molecule that could be a viable target for PD therapeutics.